COMPARISON OF MICROPLASTIC PARTICLE IN BREASTMILK STORED WITH BREASTMILK STORAGE BAG ON DIFFERENT TEMPERATURE - Susetio, Mercy Mezia; Sincihu, Yudhiakuari; Steven, Steven (JURNAL WIDYA MEDIKA, 2025)
MPs are plastic particles less than 5 mm in size. MPs can enter through the mouth and into the digestive tract, circulate throughout the body's tissues including breast tissue. Research on the size of particles that can be deposited in adipose tissue has not yet been conducted. This quasi-experimental research aims to explain differences in levels of microplastic particles due to differences in processing temperatures in breast milk in storage bags. Breast milk samples were taken from breastfeeding mothers at the Mulyorejo Community Health Center, Surabaya. The breast milk was put into plastic bags for the study group and glass tubes for the control group. Samples will be separated based on breast milk storage temperature and as a control group. The sample will be extracted and examined. After that, additional inspection tests were carried out in the form of micro-FTIR. It was found that there was no significant difference in MPs particle levels with respect to differences in breast milk processing temperatures in storage bags. However, there were significant differences between the control group and the study group.